Strategy Formulation as a Political Process - Pettigrew, A (1977)
The article presents a discussion on strategic business planning as a political process. The formation of strategy in organizations is a continuous process. Specific dilemmas within the firm, or in the firm's environment, may raise the organization members' consciousness of strategy and allow financial analysts to think of strategy formulation as an intentional process built around certain discrete decisions; but strategy is being formed implicitly all the time. Choices are made and acted upon in processes involving individuals and sub-groupings, at various organizational levels, that develop into the pattern of thinking about the world, evaluating that world, and acting upon that world that is called as strategy. Study of the process of strategy formulation therefore involves analyses of both discrete and identifiable decision events and of the pathways to and outcomes of those decision events, together with the connections between successive decisions over time. Strategy formulation is contextually based. Strategy formulation can be understood as a process of political decision-making.